Integrasi Kepemimpinan Spiritual dalam Fungsi Perencanaan dan Actuating Manajemen Pendidikan Islam - Novi Aurannisa; Widya Putri Azhari (An-Nahdloh: Journal of Education and Islamic Studies, 2025)
This study explores how spiritual leadership is integrated into the planning and acting functions of management at SD Islam Ukhuwah Pandaan. A descriptive qualitative design with a case‐study approach was employed. Data were gathered through in-depth interviews with the acting principal, non-participant observations, and an analysis of school vision and mission documents, as well as annual programs. Findings reveal that planning begins with prayer and Qur’anic reflection, followed by participatory syura that converts spiritual values into measurable indicators, worship-based calendars, and performance targets. During Actuating, the principal leads through exemplary worship, collective cleanliness routines, faith-oriented teacher training, parent collaboration via online questionnaires, and technological adaptation through Qur’anic digital literacy. This value integration enhances teacher motivation and student participation despite human-resource limitations and digital-era challenges. The study concludes that spiritual leadership is effective when reinforced by strong role modelling, participatory decision making, and continuous evaluation systems.   Keywords: Spiritual Leadership, Planning, Actuating, Islamic Education Management